THE STICH TRIAL - THE IMPORTANCE OF DRUGS IN PATIENTS WITH CORONARY ARTERY DISEASE WAS HIGHER THAN EXPECTED - S. Yu. Martsevich; N. P. Kutishenko (Столичная издательская компания, 2016)
Key findings of STICH (Surgical Treatment for Ischemic Heart Failure) trial are presented. This study goal was to evaluate the role of the surgical intervention for coronary artery bypass grafting in improvement of life prognosis in patients with ischemic heart disease complicated severe heart failure.